Situation of the Yukarıköy’s Traditional Stone Masonry Houses Affected by 2017 Ayvacık Earthquakes - Ali Rıza Parsa; Ali Osman Kuruşcu (Doğal Afetler ve Çevre Dergisi)
Turkey is considered one of the most earthquake-prone countries in the world. Turkey has hosted many important civilizations in history. Some of the important structures and settlements symbolizing the socio-economic and cultural life of these civilizations have survived to the present day. Located in the rural areas of Turkey, many of the new masonry structures that continue to be constructed under the influence of the structural culture formed by the civilizations are also under the influence of earthquake loads. February-March 2017 Çanakkale/Ayvacık-based earth-quakes caused significant damage to the traditional masonry structures. The region in which Gülpınar based earthquakes took place has a significant historical background. The geography of the region where the earthquake took place hosts different civilizations from the chalcolithic period to the present. The examination of this region is important in that it is an earthquake region as well as having a noteworthy historical background. This study examines the behavior of the masonry structures damaged by the mentioned earthquakes, and the causes of damage. The study also reveals the importance of the architectural design of structures under the effect of the earthquake to its users. In the period of new settlement that will take place after the earthquake, in the light of the analyzes, suggestions have been made in order to bring out the structures that are comfortable, safe, and sustainable, considering the structural culture of the region.